Early school leaving and foreign-origin students in Spain: an invisible problem? - Silvia Carrasco; Jordi Pàmies; Laia Narciso (Anuario CIDOB de la Inmigración, 2018)
Spain has one of the highest rates of early leaving from education and training (ELET) in the EU and the greatest polarisation by origin. This paper presents and analyses some results from the project Reducing Early School Leaving in Europe (RESL.eu), which has researched the systemic, institutional and individual processes and factors that lead to the premature interruption of education. Based on the sample of the Spanish study carried out in two regions of Catalonia, this work investigates the higher incidence of ELET among foreign-origin students. Improving support for educational transitions and providing more inclusive routes emerge as the most important challenges in order for schooling to really promote the social integration of young people of foreign origin.